2020
DOI: 10.1186/s13148-020-0820-0
|View full text |Cite
|
Sign up to set email alerts
|

An epigenome-wide association study of posttraumatic stress disorder in US veterans implicates several new DNA methylation loci

Abstract: Background: Previous studies using candidate gene and genome-wide approaches have identified epigenetic changes in DNA methylation (DNAm) associated with posttraumatic stress disorder (PTSD). Methods: In this study, we performed an EWAS of PTSD in a cohort of Veterans (n = 378 lifetime PTSD cases and 135 controls) from the Translational Research Center for TBI and Stress Disorders (TRACTS) cohort assessed using the Illumina EPIC Methylation BeadChip which assesses DNAm at more than 850,000 sites throughout the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 72 publications
3
56
0
3
Order By: Relevance
“…Of the 172 CpGs included in the DNAmPACKYRS metric, the cg05575921 site, corresponding to the Aryl Hydrocarbon Receptor Repressor (AHRR) gene, was of particular interest in light of recent evidence suggesting a role in post-traumatic stress disorder(31,32). To explore if the cg05575921 methylation site might be contributing to differences in DNAmPACKYRS between MDD and HC independent of smoking exposure, we assessed differences in cg05575921 methylation 1) associated with smoking, and 2) between MDD and HC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 172 CpGs included in the DNAmPACKYRS metric, the cg05575921 site, corresponding to the Aryl Hydrocarbon Receptor Repressor (AHRR) gene, was of particular interest in light of recent evidence suggesting a role in post-traumatic stress disorder(31,32). To explore if the cg05575921 methylation site might be contributing to differences in DNAmPACKYRS between MDD and HC independent of smoking exposure, we assessed differences in cg05575921 methylation 1) associated with smoking, and 2) between MDD and HC.…”
Section: Resultsmentioning
confidence: 99%
“…Our pattern of findings is also consistent with those of Lu et al in their original publication on GrimAge, where they demonstrated that DNAmPACKYRS predicted lifespan in never smokers(15), suggesting that this composite measure of methylation at 172 CpG sites reflects changes in underlying biological processes not specific to tobacco use. Of these sites, the cg05575921 site and its associated gene – the Aryl Hydrocarbon Receptor Repressor (AHRR) – stand out as potentially relevant to the pathophysiology of psychiatric disease(31,32) and aging(36,37). We compared methylation at this site between MDD and HC and found no significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two recently published studies have provided insight into this question. The first sought to identify DNA methylation differences associated with PTSD in blood of 378 PTSD cases and 135 controls from the Translational Research Center for Traumatic Brain Injury and Stress Disorders (TRACTS) cohort 25 . This study used a methylation-based score for smoking as a covariate, and still reported a significant association between PTSD and cg05575921 ( AHRR ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar epigenetic signatures have been discovered in humans with a history of childhood abuse [ 68 ]. Epigenetic biomarkers have been developed for diagnosis of metabolic diseases and, perhaps of most interest here, neuropsychiatric disorders in humans [ 69 , 70 , 71 ]. In pigs, the influence of early-life stress has been extensively studied and documented (reviewed in [ 72 ]; however, with few exceptions [ 73 ], the epigenome alterations remain largely unexplored.…”
Section: Biomarkers For Stress Resilience In Farm Animalsmentioning
confidence: 99%